Enhanced photodegradation of dyes and mixed dyes by heterogeneous mesoporous Co–Fe/Al2O3–MCM-41 nanocomposites: nanoparticles formation, semiconductor behavior and mesoporosity. Issue 96 (3rd October 2016) - Pradhan, Amaresh C.; Sahoo, Malaya K.; Bellamkonda, Sankeerthana; Parida, K. M.; Rao, G. Ranga
Abstract : Fabrication of mono and bimetallic nanoparticles by in situ sol–gel cum hydrothermal method for photo degradation of dyes and mixed dyes. Abstract : In situ loading of mono and bimetallic nanoparticles in the framework of mesoporous Al2 O3 –MCM-41 and its effect on the photo-Fenton degradation of dyes and mixed dyes has been reported in the present study. The nanocomposites are synthesized by in situ sol–gel cum hydrothermal method where oleic acid has been used as capping agent for mono and bimetallic nanoparticles. Materials were characterized by high and low angle XRD, N2 sorption, and HRTEM to evaluate mesoporosity, morphology and textural properties. The photoluminescence (PL) study and band gap energy measurement reveals suppression of e − and h + recombination and semiconductor behaviour of bimetallic/Al2 O3 –MCM-41 in visible region. Both the processes of photo-Fenton and photocatalysis takes place over mesoporous Co–Fe/Al2 O3 –MCM-41 nanocomposite, which is found to be an efficient material with 100% efficiency for the degradation of dyes and mixed dyes (100 mg L −1 ) at pH 10 in just 60 minutes. Framework mesoporosity, nanoparticle morphology of the nanocomposite, semiconductor behavior, lowering of the electron–hole recombination and the formation of a large number of ˙OH radicals are the crucial factors for swift degradation of dyes and mixed dyes by mesoporous Co–Fe/Al2 O3 –MCM-41 nanocomposite.